Male mate choice for large gravid spots in a livebearing fish. (27th September 2019) - Ogden, Hannah J P; de Boer, Raïssa A; Devigili, Alessandro; Reuland, Charel; Kahrl, Ariel F; Fitzpatrick, John L
Abstract: Male mate choice occurs in a wide range of species, and males can increase their reproductive success by distinguishing between females based on their fecundity (e.g., large body size) or their expected sperm competition risk (e.g., virgins). However, patterns of male mate choice could be mitigated by variation in female physiological receptivity, as males can benefit by directing their mating efforts toward females that are at a point in their reproductive cycle when fertilization probability is highest. Here, we perform three experiments to assess whether male mate choice is influenced by cues of female physiological receptivity, fecundity, or sperm competition risk in the pygmy halfbeak ( Dermogenys collettei ), a small livebearing fish. Female halfbeaks possess a "gravid spot"—an orange abdominal marking that is caused by pigmentation of the females' skin and variation in embryo development and pigmentation during pregnancy. We show that gravid spot size increases toward parturition and is largest right before giving birth, independent of abdominal width or body size. Males consistently chose females with large gravid spots over females with small gravid spots. In contrast, males did not prefer larger females over smaller females or virgin females over mated females. As female halfbeaks store sperm prior to fertilizations, we suggest that males use the size of the gravid spot as a cue to direct their mating efforts to those females where the chance of fertilization is highest. Abstract : When is it a good time to mate? In fish that give birth to live young, females have a mark on their abdomen, a "gravid spot, " that changes in size over their reproductive cycle. Using a livebearing fish, the pygmy halfbeak, we show males pay attention to gravid spot size, going out of their way to court females with the largest gravid spots. We suggest that gravid spots provide information about female receptivity.